COMPARISON BETAXOLOL AND METOPROLOL TARTRATE THERAPIES IN PATIENTS WITH ARTERIAL HYPERTENSION ASSOCIATED WITH STABLE ANGINA - A. A. Anderzhanova; J. V. Gavrilov; V. A. Sulimov (Рациональная фармакотерапия в кардиологии)
Aim. To compare antihypertensive, antianginal and antiischemic efficacy of β1-selective adrenoblockers (betaxolol and metoprolol tartrate) in patients with arterial hypertension (HT) of 1-2 degree associated with stable angina class II.Material and methods. 100 patients (aged 23-66 y.o.) with HT associated with stable angina or without angina were involved in the study. Patients were randomized into 2 groups (G1 and G2). G1 patients were treated with betaxolol, and G2 patients – with metoprolol tartrate. Ambulatory BP and electrocardiogram monitoring, exercise stress-test, echocardiography, evaluating of respiratory function, blood analysis was performed initially and in 30 and 90 days of treatment.Results. Target BP level was reached in 44 (88%) patients treated with betaxolol (average daily dose 10±4 mg). 34 patients of G1 took 10 mg daily. Target BP level was reached in 41 (82%) patients treated with metoprolol tartrate (average daily dose 150±27 mg). 30 patients of G2 took 150 mg daily. Exercise tolerance increased and a number of ischemic ST segment depressions reduced significantly in both groups. There were no significant differences in antihypertensive, antianginal, and antiischemic efficacy between groups.Conclusion. Betaxolol advantage is an ability to maintain target BP level more than 24 hours. A possibility to take betaxolol once a day raises patient’s compliance with therapy.